Workforce and Contents of Home Dental Care in Japanese Insurance System - Yoshiaki Nomura; Ayako Okada; Erika Kakuta; Ryoko Otsuka; Hideaki Saito; Hiroshi Maekawa; Hideki Daikoku; Nobuhiro Hanada; Tamotsu Sato (International Journal of Dentistry)
Background. In Japan’s super-aging society, it is required to establish a home dental service provision system. It is necessary to analyze the current state of visiting dentistry. Methods. A cross-sectional survey was conducted using a self-administered postal mail questionnaire distributed to all members of the Iwate Dental Association. We analyzed the implementation status of dental care at home/nursing facilities, the number of dental clinic staff, and the contents of dental home care. Correspondence analysis, item response theory, and zero-inflated model were used for the analysis. Results. Of the 354 dental clinics, 187 (52.8%) performed visiting dental care and 195 (55.1%) implemented dental care in a nursing home. Visit dentistry was mainly performed by part-time workers. Denture treatment and oral care were common treatments for dental home care. Conclusion. More than half of the dental clinics did not offer visiting dentistry. In order to fully provide dental visiting services, infrastructure development is necessary. Specifically, human resources are most important, even if they are part-time workers.